1994
DOI: 10.1364/ol.19.001979
|View full text |Cite
|
Sign up to set email alerts
|

Compression-tuned single-frequency Bragg grating fiber laser

Abstract: Compressive stress has been used to continuously wavelength tune a single-frequency Bragg grating fiber laser over 32 nm without mode hopping. A master-oscillator/power-amplifier configuration and active noise reduction were implemented to maintain a constant, low-noise, 3-mW lasing power over the tuning range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(43 citation statements)
references
References 6 publications
0
42
0
1
Order By: Relevance
“…Given the physical constraints of this system, tuning is achieved by stretching the fiber, despite the limited tuning range for stretched as opposed to compressed gratings. (In the 1 .55 im regime stretching leads to a tuning range of 10 nm as opposed to 32 nm for compression [2].) This encoder architecture also requires significant physical separation between gratings to attach the piezoelectric devices, limiting the bit rate.…”
Section: Optical Ffh-cdmamentioning
confidence: 99%
See 1 more Smart Citation
“…Given the physical constraints of this system, tuning is achieved by stretching the fiber, despite the limited tuning range for stretched as opposed to compressed gratings. (In the 1 .55 im regime stretching leads to a tuning range of 10 nm as opposed to 32 nm for compression [2].) This encoder architecture also requires significant physical separation between gratings to attach the piezoelectric devices, limiting the bit rate.…”
Section: Optical Ffh-cdmamentioning
confidence: 99%
“…Define Rm,p as the average cross-correlation for any time shift between the two codes Cmand c, = 21Rm,p(S) (2) If we further average over all code pairs, we arrive at the average cross-correlation…”
Section: Ber Performancementioning
confidence: 99%
“…The researches above applied optical fibers in crack monitoring and results showed that optical fibers have potential in crack monitoring. However, all the fibers in the above researches are silica fibers which are brittle (their elongation rates only about 1%) [12], so they are easy to break in real applications and only small cracks can be monitored. Therefore, the brittleness of silica fibers limits the application of above researches.…”
Section: Introductionmentioning
confidence: 99%
“…1,[10][11][12][13] This type was chosen here, because fiber lasers can be designed with the excellent mode-hop-free tuning characteristics needed for use with the OFDR system. This approach was also chosen here because the stress-tuning hardware can be compact and lightweight, which is important in view of the high cost of launching payloads into space.…”
Section: Introductionmentioning
confidence: 99%